A re‐evaluation of hemispheric asymmetries in herbivory: a response to Kozlov & Klemola 2017. (20th September 2017) - Zhang, Shuang; Zhang, Yuxin; Ma, Keming
Summary: Kozlov & Klemola ( Journal of Ecology, 105, 2017: 000‐000) argued that our conclusion about hemispheric asymmetries in herbivory is not supported after the replacement of data points extracted from Moles & Westoby ( Oikos, 90, 2000: 517–524.). To re‐evaluate the asymmetries in herbivory, we analysed the revised dataset according to Kozlov & Klemola's (2017) suggestion, as well as the dataset used in Kozlov et al . ( Global Ecology and Biogeography, 24, 2015: 1126–1135.). All the analyses showed that herbivory decreased with latitude only in the Northern hemisphere, but in the Southern hemisphere, herbivory showed no relation to latitude. Model selection showed that in both datasets, hemisphere is a key determinant of herbivory, with Southern hemisphere having higher levels of herbivory than the Northern hemisphere. Synthesis . Based on currently available data collected from publications, we found evidence for hemispheric asymmetries in herbivory. This conclusion is unlikely to change even when the controversial data points are replaced. Abstract : Based on currently available data collected from publications, we found evidence for hemispheric asymmetries in herbivory. This conclusion is unlikely to change even when the controversial data points are replaced.